Work Unit Efficiency Analysis Using Integration Of Data Envelopment Analysis And Logic Model Methods - Fajar Al-Hadi; Rahadi Nugroho (Jurnal Ekonomi, 2024)
This research aims to assess the efficiency of work units by integrating data envelopment analysis and logic model methods. By collecting data for 2 years, fluctuations in the efficiency of work units can be seen in terms of resources, processes, outputs and outcomes. For work units that are not yet efficient, efficient work units can be used as a benchmark.